Photobiomodulation of in-vitro cell culture using light emitting diodes (LEDs) - Prabhu, Akshaya (2018)
Photobiomodulation has emerged as a form of alternative medicine through the therapeutic application of light, in the form of lasers and LEDs. This non-invasive approach has been used in many clinical applications to repair and heal acute tissue injuries, reduce pain and inflammation as well as to produce vital structural proteins that are found in the human skin. However, majority of the applications for photobiomodulation is still aimed at in-vivo applications. Hence in this project, in line with the group’s focus on cell manufacturing, a Desktop Photostimulation System (DPS) has been developed to be able to perform in-vitro photostimulation on cells to enhance its activity and eventually achieve a higher total cell population. The limits of photostimulation using the DPS was therefore investigated using WS1 fibroblast cells, with the chosen parameters from literature review that were highlighted to have worked positively on fibroblast cells. The longer irradiation duration of 750 seconds for all irradiation intensities 2, 3, 4 mW/cm2 has been observed to have pushed the final cell counts positively above that of control.